Analysis of antioxidant properties of plants extracts - Laguta, I.V.; Stavinskaya, О.N.; Dzyuba, О. I.; Ivannikov, R.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Ethanol extracts from leaves of 21 plants are prepared, and their antioxidant characteristics are investigated, by using the Folin-Ciocalteu method and the DPPH test. Some of these extracts are found to possess high antioxidant properties, with the extracts of Vitex, Magnolia, Stevia, Actinidia being especially active in test reactions. The antioxidant properties of the plants cultivated both ex situ and in vitro are found to be comparable with one another. Thus, these plants may be considered as potentially interesting raw materials for the production of effective antioxidants of the natural origin.